The Effect of Mobile Learning Posters on Students' Creative Thinking Skills in Secondary Schools: An Islamic Educational Perspective - Husna, Annisa Nur Nadhilla; Mulyanto, Mulyanto; Yulianto, Nanang (Suhuf: International Journal of Islamic Studies, 2026)
Background: This study addresses the challenge of optimizing students’ creative thinking skills, which are often constrained by limited innovation in learning media within the school environment. The lack of interactive learning media tends to reduce students’ active engagement during the learning process. Objective: This study aims to examine the effect of poster-based m-learning digital learning media on the creative thinking skills of eleventh-grade students. Methodology: The research employed a quantitative method with a quasi-experimental approach using a nonequivalent control group pretest–posttest design. Data were collected through questionnaires and creative thinking tests and analyzed using inferential statistics through a t-test. Results: The results indicate that the t-count value exceeds the t-table value, meaning that the alternative hypothesis is accepted. These findings demonstrate that the use of m-learning media significantly improves students’ creative thinking skills, while interactive and multimedia features increase students’ engagement in understanding poster design elements and principles. Conclusion and Implications: Overall, mobile-based learning media are effective in improving students’ creative thinking skills while also supporting the development of independence, responsibility, and ethical use of technology in learning.